2020
DOI: 10.7196/sajch.2020.v14i3.01723
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of childhood Hodgkin lymphoma in sub-Saharan Africa: A report from the French-African Paediatric Oncology Group (GFAOP)

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0. Hodgkin lymphoma (HL) is a B-cell line lymphoma, characterised histologically by the presence of large, atypical cells called Reed-Sternberg cells. The first histological description dates back to 1832 by Thomas Hodgkin. [1] Epstein-Barr virus (EBV) is an important factor in the pathogenesis of HL and it is detected in Reed-Sternberg cells in the vast majority of HL specimens from developing countries, but much less frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…1 The 1-year survival of 90% for Hodgkin lymphoma in this study supports previously published data for the group of 106 cases where 3-year survival was 82%. 35 Similarly, a previous GFAOP study found 3-year survival of 72% for 161 nephroblastoma cases.…”
Section: Discussionmentioning
confidence: 84%
“…1 The 1-year survival of 90% for Hodgkin lymphoma in this study supports previously published data for the group of 106 cases where 3-year survival was 82%. 35 Similarly, a previous GFAOP study found 3-year survival of 72% for 161 nephroblastoma cases.…”
Section: Discussionmentioning
confidence: 84%
“…An 80% OS was achieved in a study of patients in Burkina Faso, Cameroon, Mali, Madagascar and Senegal, low-income countries without access to radiotherapy. 20 Although seven patients were inappropriately treated on the intermediate-risk rather than the high-risk arm, the OS is still high.…”
Section: Discussionmentioning
confidence: 99%
“…The role of radiotherapy in HL continues to be explored, and research efforts are ongoing to better define the small group of patients that require this modality for cure. An 80% OS was achieved in a study of patients in Burkina Faso, Cameroon, Mali, Madagascar and Senegal, low‐income countries without access to radiotherapy 20 …”
Section: Discussionmentioning
confidence: 99%
“…100,101 The GFAOP has executed and published multiple prospective clinical trials, including several trials in which treatment protocols developed in Europe were modified by the group for implementation in resource-poor regions. 102 For example, implementation of the SIOP 2001 protocol for Wilms tumor demonstrated one of the highest survival rates in sub-Saharan Africa. 103,104 The GFAOP has asserted its commitment to leveraging multidisciplinary and multicenter support to construct the necessary infrastructure for future trials, and a third prospective multicenter study of a novel adapted treatment regimen was recently published.…”
Section: Pediatric Oncology Clinical Trial Collaborative Groups By Re...mentioning
confidence: 99%